2011
DOI: 10.1155/2011/864710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic model based on Raman spectra of normal, hyperplasia and prostate adenocarcinoma tissuesin vitro

Abstract: Abstract. This study evaluated the use of Raman spectroscopy to identify the spectral differences between normal (N), benign hyperplasia (BPH) and adenocarcinoma (CaP) in fragments of prostate biopsies in vitro with the aim of developing a spectral diagnostic model for tissue classification. A dispersive Raman spectrometer was used with 830 nm wavelength and 80 mW excitation. Following Raman data collection and tissue histopathology (48 fragments diagnosed as N, 43 as BPH and 14 as CaP), two diagnostic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(65 reference statements)
0
11
0
Order By: Relevance
“… 22 , 56 Finally, the band from 1760 to , influenced by DNA/RNA, proteins and phospholipids, is also present on benign prostatic hyperplasia. 23 , 56 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 22 , 56 Finally, the band from 1760 to , influenced by DNA/RNA, proteins and phospholipids, is also present on benign prostatic hyperplasia. 23 , 56 …”
Section: Discussionmentioning
confidence: 99%
“… 25 28 Furthermore, with the development of optical fiber RS probes, this technique is moving to clinical applications 29 ; different optical probe designs have been used for in-vivo tissue characterization (in human and animal models) for targeting skin cancer in open surgeries, 30 minimally invasive diagnosis of lung cancers, 31 bladder cancer detection using a superficial and nonsuperficial Raman probes, 32 observation of skin changes after breast cancer treatment, 33 and others. 34 37 In prostate applications, it has been used for ex-vivo characterization and in-vivo margin detection, 19 , 20 , 23 , 38 , 39 but, to the best of our knowledge, so far, not for real-time in-vivo prostate tumor burden confirmation, which can provide great benefit for clinical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Stone et al (2007) , prostate cancer cells were found to have a higher nuclear/cytoplasmic ratio and higher DNA, choline and glyceric acid concentrations than prostate hyperplastic tissue. Based on the differences in the biochemical composition like proteins, lipids, nucleic acids and amino acids, and corresponding Raman bands in normal, BPH and prostatic adenocarcinoma, Lopes et al (2011) developed a diagnostic algorithm combined PCA with Mahalanobis distance discriminant analysis to identify normal, BPH and adenocarcinoma tissues from in vitro prostate biopsy fragments and then developed a spectral diagnostic model for tissue classification. Prostate lesion samples were classified into three histological groups in this model with 100% sensitivity and specificity.…”
Section: Application In Prostate Diseasesmentioning
confidence: 99%